PEREBUTAN NARASI PENYEBAB BENCANA: SEMANTIK KONSEPTUAL MENURUT CHAER BERITA BANJIR BALI - Hariz Maulana Atha Aufa; Sri Kumala Dewi; Widyah Rusmaningrum; Ingghar Ghupti Nadia Kusmiaji (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study examines the use of conceptual meaning in news reporting on the causes of flooding in Bali in national online media. Mass media employ terms such as flood, extreme rainfall, and land-use change to explain disaster events in a factual manner. This study aims to describe the use of conceptual meaning according to Chaer in framing the causes of flooding in Bali. The research method used is descriptive qualitative, with online news texts as the data source. Data were collected through observation and note-taking techniques, while data analysis focused on the basic meanings of the words and phrases used. The results show that news coverage of the Bali floods is dominated by conceptual meanings that are objective and informative, thereby shaping readers’ rational understanding of the causes of the disaster